2013
DOI: 10.21859/isv.7.1.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Serological Detection of Canine Distemper Virus (CDV) in Rural Dogs, Iran

Abstract: Background and Aims: Canine distemper (CD) is a deadly infectious disease of Canidae family. CD is a multi-systemic viral disease and is specified by wide range of clinical symptoms. The manifestations are not always indicative of CD, therefore a laboratory confirmation is necessary for suspected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The positivity rate of this technique in our study was 8.86%. In other studies, the molecular positivity was 15% in Iran [ 34 ], 21% in India [ 35 ], 24.88% in China [ 36 ], 30.66% in Hungary [ 37 ], and 73.74% in Argentina [ 38 ]. Many studies have confirmed the high sensitivity and specificity of RT-PCR in the detection of canine distemper virus in different clinical samples, including serum, urine, and conjunctival swabs, as well as in confirming sub-acute and chronic stages of the disease in cases of poor viral shedding [ 35 , 39 - 40 ].…”
Section: Discussionmentioning
confidence: 95%
“…The positivity rate of this technique in our study was 8.86%. In other studies, the molecular positivity was 15% in Iran [ 34 ], 21% in India [ 35 ], 24.88% in China [ 36 ], 30.66% in Hungary [ 37 ], and 73.74% in Argentina [ 38 ]. Many studies have confirmed the high sensitivity and specificity of RT-PCR in the detection of canine distemper virus in different clinical samples, including serum, urine, and conjunctival swabs, as well as in confirming sub-acute and chronic stages of the disease in cases of poor viral shedding [ 35 , 39 - 40 ].…”
Section: Discussionmentioning
confidence: 95%
“…Although real-time PCR test is an expensive one, it has begun to take the place of conventional PCR since it has a high specificity and sensitivity and requires no process following the reaction; thus the risk of contamination is low , Pawar et al 2011. In diagnosing CDV, quite many samples can be taken from animals such as blood (Shin et al 2004, ocular and nasal swab (Saito et al 2006, urine (Shin et al 2004), vaginal swab (Fischer et al 2013), lung (Headley et al 2000, Shin et al 2004, stomach (Headley et al 2000), kidney (Namroodi et al 2013) and bladder (Richter and Motze 1970) tissues. Kim et al (2006) detected positivity at an important high rate in ocular swab samples of seven dogs infected experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…(12)(13)(14)(15) Numerous studies report the prevalence of the distemper in different countries. (16)(17)(18)(19)(20)(21) In most of these reports, the prevalence of the disease has been evaluated by serological methods, but there are few reports that reveal the accurate fatality and mortality rates of distemper in dogs. One study on necropsy cases reported that 11.7 % of patients were due to distemper.…”
Section: Discussionmentioning
confidence: 99%